The concept of fiction: revisiting a complex notion (El Taco en la Brea, 2024)
This article aims to synthesize some of the most recent theoretical contributions developed around the concept of fiction, based on the consideration that, despite constituting a central concept that conditions, albeit implicitly, research on literature, is not usually given a preponderant space in the chairs of literary theory. Two central axes or axioms structure the reflections developed here: first, that fictional discourse institutes a conditional regime in which the demands of verismo and verifiability are suspended; secondly, that the institution of this conditional status depends more on the external pragmatic framing than on the intrinsic characteristics of the texts/fictional artistic products. In other words, there are not two modalities of representation, one fictional and the other referential, but it is the pragmatic framing that suspends the direct referentiality of the discourse, instituting the imaginary terrain that we call «Fiction».
Keywords: fiction; Literary Theory; pragmatic framing; modeling; representation